Neuroleptic malignant syndrome – a case report - Makuch, Marcin; Makuch, Marcelina; Kordyga, Aleksandra; Trojnar, Marcin (Journal of Education, Health and Sport, 2019)
Neuroleptic malignant syndrome (NMS) is rare, but potentially lethal complication associated with the use of neuroleptic agents. NMS is most often observed after high-potency first-generation neuroleptic agents. NMS is characterised by a distinctive clinical syndrome including: hyperthermia, muscular rigidity, mental status change, autonomic disability. The most common laboratory finding is elevated serum CK. The management of patients with NMS demands aggressive care and discontinuing of the causative agent. A 49-year-old patient with recurrent depressive disorders is presented. NMS developed following the increase in haloperidol dose and concomitant use of olanzapine. The treatment with bromocriptine and lorazepam resulted in a prompt recovery.